Increasing Corneal Donations in a Private Hospital: The Impact of Improvement Strategies on Hospital Organ Procurement Teams - Caldas, Juliana; Piropô, João; Pires, Isabella; Costa, Vanessa; Rocha, Eduardo; Mendes, Ana Verena (Brazilian Journal of Transplantation, 2026)
Objectives: In recent years, there has been a notable increase in cornea donations in the state of Bahia, Brazil. However, this has been accompanied by an exponential rise in the number of individuals on the waiting list for corneal transplants, resulting in a growing deviation from the goal of achieving a “zero waitlist.” To improve the organ and tissue procurement process, the hospital organ donation teams for transplantation (equipes hospitalares de doação para transplantes [E-DOTs]) have been established. Despite their critical role in expediting this process, significant unfamiliarity with their operation and impact persists. This study aimed to evaluate cornea procurements at Hospital São Rafael (HSR) from 2019 to 2025 and assess the impact of a bundle of improvement actions implemented in December 2019, including the management of quality indicators in 2022, by comparing outcomes before and after these measures. Methods: This descriptive, retrospective, ecological study analyzed HSR’s cornea procurement data from 2019 to 2025 to evaluate the impact of a bundle of improvement measures. Key outcomes and process indicators were compared before and after implementation. The bundle, developed by a multidisciplinary team, included expanding committee membership, providing early psychological support to families, training healthcare staff to identify potential donors, enhancing E-DOT members’ communication skills, and actively managing key indicators such as donor identification, family consent, and effective donations. Results: Analysis of E-DOT indicators demonstrated that, in absolute numbers, cornea donations increased from one cornea in 2019 (team reorganization) to 14 donors in 2021 (before the implementation of the bundle) and to 35 in 2025. The identification rate was 33% in 2021, 66% in 2022, and 88% in 2025. Conclusion: The implementation of measures to improve the identification and procurement of corneas, along with effective management of the quality indicators of the E-DOT, resulted in a significant increase in cornea donation rates at a private hospital. It is concluded that it is crucial to strengthen local E-DOTs with dedicated hours, continuous presence of members, and ongoing training. These improvements will enable an increase in the number of cornea donors and, consequently, an increase in the number of corneal transplants performed.